Assessment of Asthma Control and Quality of Life among Asthmatic Patients Attending Armed Forces Referral and Teaching Hospital, Addis Ababa, Ethiopia - Tesfalidet Gebremeskel Zeru; Ephrem Engidawork; Alemseged Beyene Berha (Pulmonary Medicine)
Background. The primary goal of asthma management is to achieve good asthma control. However, poor patient-physician communication, unavailability of appropriate medications, and lack of long-term goals have made asthma control difficult in developing countries. Poor assessment of asthma control and quality of life is a major cause of suboptimal asthma treatment worldwide, and information regarding this issue is scanty in developing countries like Ethiopia. This study thus attempted to assess the level of asthma control and quality of life in asthmatic patients attending Armed Forces Referral and Teaching Hospital. Methods. A cross-sectional study comprising 184 physician-diagnosed asthmatic patients was conducted using interview, chart review, and prescription assessment. Asthma control was assessed using Asthma Control Test, while asthma quality of life was assessed using Mini-Asthma Quality of Life Questionnaire (mini-AQLQ). Spearman’s rank correlation analysis was performed to understand the relationship between mean mini-AQLQ score and asthma control. Receiver operating characteristic curve analysis was performed to establish cut-off values for mini-AQLQ. Results. Asthma was uncontrolled in 67.9% subjects. There was a strong correlation between asthma control and quality of life (rs=0.772; P<0.01). A cut-off value for the quality of life was established at 4.97. Majority of the patients were taking two or three antiasthmatic drugs. Oral tablet and inhaler short-acting beta agonists (SABA) were the frequently combined drugs. Uncontrolled asthma was associated with middle-aged adults (adjusted odds ratio AOR=6.31; 95% CI: 2.06, 19.3; P=0.001), male gender (AOR=0.38; 95% CI: 0.15, 0.98; P=0.044), married (AOR=0.24; 95% CI: 0.08, 0.78; P=0.017), comorbidities (AOR=0.23; 95% CI: 0.09, 0.61; P=0.003), and oral SABA use (AOR=0.22; 95% CI: 0.09, 0.59; P=0.003). Male gender (AOR=0.36; 95% CI: 0.16, 0.84; P=0.018), intermittent asthma (AOR=0.18; 95% CI: 0.04, 0.86; P=0.032), use of oral corticosteroids (AOR=0.22; 95% CI: 0.06, 0.73; P=0.013), and SABA (AOR=0.39; 95% CI: 0.17, 0.89; P=0.026) were found to have a significant association with poor asthma-related quality of life. Conclusion. The findings collectively indicate asthma remains poorly controlled in a large proportion of asthma patients in the study setting. Moreover, quality of life appears to be directly related to asthma control. Healthcare providers should therefore focus on asthma education with an integrated treatment plan to improve asthma control and quality of life.